Differential regulation of C-C chemokines during fibroblast-monocyte interactions: adhesion vs. inflammatory cytokine pathways - C. Zickus; S. L. Kunkel; K. Simpson; H. Evanoff; M. Glass; R. M. Strieter; N. W. Lukacs (Hindawi Limited, 1998)
The cell-to-ce ll interactions during chronic inflammatory diseases likely contribute to leukocyte accumulation leading to increased pathology and organ dys -function. In particular, there is a paucity of information relating to the maintenance of chronic fibrotic diseases . Using a lung fibroblast line and enriched monocyte populations , we have investigated the activational events which contribute to the production of two C-C chemokines , macrophage inflammatory protein-1 alpha (MIP-1α ) and monocyte chemoattractant protein-1 (MCP-1), during fibroblas tmonocyte interactions . Neither the fibroblast cell line (16 lu) nor isolated monocytes alone produced significant levels of MIP-1α or MCP-1. However, when isolated monocytes were layered onto 16 lu fibroblas tmonolayers as ignificant increase in MIP-1α and MCP- 1 production was observed. The use of fixed cell populations indicated that the MIP-1α was derived from monocytes and MCP-1 from both cell populations. To examine the molecules which wer erequired for chemokine production during the interaction, specific antibodies were used in the co-cultures . Blocking β3-integrin interactions s ignificantly inhibited MIP-1α production. In contrast, beta-integr in interactions had no effect on the MCP-1 production, while, neutralization of TNF significantly decreased MCP-1 production during the co-culture . These data indicate that fibroblast-monocyte inte ractions induce chemokine production through different mechanisms and a combination of these responses may contribute to the maintenance of the mononuclear cell accumulation during diseaseprogression.